Sex is not an independent predictor of 90-day outcomes after mechanical thrombectomy in Chinese patients with acute ischemic stroke: a prospective cohort study - Liu, Quan; Liu, Sijia; Yang, Jialin; He, Qing (Frontiers in Surgery, 2026)
ObjectiveTo explore the impact of sex difference in the 90-day favourable outcome after mechanical thrombectomy(MT) with acute ischaemic stroke(AIS).MethodsWe consecutively enrolled AIS patients treated with MT from the First Affiliated Hospital of Chengdu Medical College and Nanjing First Hospital between June 2015 to June 2022. According to the inclusion and exclusion criteria. Patients were divided into two groups by sex, and detailed demographic, laboratory examination, imaging examination and clinical data were collected. The primary outcome (favourable 90-day outcomes, mRS 0-2) was prospectively followed up. Univariate and multivariate logistic regressions were performed with SPSS 26.0.ResultsAmong 334 patients analyzed (198 male, 136 female), females were significantly older (median age: 76.0 vs. 68.5 years, P < 0.001), had higher admission glucose levels (7.3 vs. 6.5 mmol/L, P = 0.031), and higher prevalence of atrial fibrillation (47.1% vs. 26.3%, P = 0.001). Male patients had higher smoking rates (59.6% vs. 5.1%, P < 0.001). In univariate analysis, female sex was associated with lower odds of favorable outcome (OR 0.520, 95% CI 0.323–0.836, P = 0.007). However, after adjustment for age, baseline NIHSS, 24-hour NIHSS, mTICI 2b–3, hemorrhagic transformation, smoking, and fasting glucose, sex was not an independent predictor of 90-day favorable outcome (aOR 0.97, 95% CI 0.451–2.081, P = 0.939).ConclusionSex and 90-day favorable outcomes in Chinese patients with AIS undergoing MT are not independently associated.